KARAKTERISTIK BETON MUTU K-200 MENGGUNAKAN SERAT 2% BERAT VOLUME DENGAN VARIASI RASIO L/D - Tri Mulyono (Politeknik Negeri Semarang, 2022)
This research aims to determine the characteristics of K-200 concrete according to Permen PUPR No. 28/PRT/M/2016 article B.06, using steel fibers (bendrat wire) with 2% steel fiber by weight of concrete volume and variations in the L/D ratio through laboratory tests. The total population is 12 specimens with a sample of compressive strength 5 specimens and split tensile strength 4 specimens for each treatment which is a random sample, i.e.: A (reference concrete); B, C, D, and E for concrete with 2% fiber and L/D ratio of 50; 62.5; 75 and 87.5. The test results of concrete materials meet the SNI. The significance level of 0.05 indicates that the test data are normal distribution and uniform. The hypothesis result shows that there is a difference between the reference concrete and the concrete fiber with variations L/D. The unit weight of concrete between the reference concrete and the concrete with variations of L/D is slightly different. The slump value decreases with the L/D ratio. Characteristics of the concrete increase up to L/D 75. Based on the design of K-200 concrete per-as Permen PUPR No. 28/PRT/M/2016 article B.06, compressive strength, split tensile strength, and flexural strength for reference concrete are 17,316 MPa, 2,317 MPa, and 3,083 MPa, greater than 35,9%, 43,8%, and 28,7% of design. Fiber concrete with variation of L/D, compared with reference concrete is greater than 32,7%, 39,7% and 26,2%.